Tourist perceptions of forestry in the coastal landscape of the Westfjords - Lange, Carla M., 1986- (2016)
Verkefnið er unnið við Háskólasetur Vestfjarða Verkefnið er lokað til 31.12.2018. In the Westfjords of Iceland, afforestation, the establishment of trees in a previously treeless landscape, is taking place in order to counteract some environmental and economic challenges the region is facing. The regions scenic coastal landscape attracts a steadily rising number of visitors, making tourism increasingly important as a source of income. Afforestation can significantly alter an environments aesthetic character, making it susceptible to public judgement especially in landscapes of high scenic value. A knowledge gap in the study of social acceptance of afforestation efforts in the Westfjords has been noticed. The objective of this project was to better understand the perceptions and preferences tourists have with regards to afforestation in the coastal landscape. The findings contribute to better integration of the tourism and forestry sectors and subsequently better founded landscape-related decision-making. Data on visitors' opinions was collected using photo-based questionnaires. Images displayed various forest design approaches. It was found that the coastal landscape is considered visually attractive. It is presently neither positively or negatively affected by the extent of forestry activity. Opposition was voiced towards afforestation activities that modify the characteristic open landscape of the Westfjords, by blocking scenic views or diminishing naturalness. Naturalness was found to be the most important factor determining the attractiveness of forests. A gap between naturalness as perceived by tourists and ecological naturalness became apparent. Suggestions for ways to integrate afforestation practices with tourism in the Westfjords were made. They include policy and education based steps. There is a pronounced need for future research of the social acceptability of forestry in the Westfjords.